The perceived quality of wooden building materials : A systematic literature review and future research agenda - Harju, Charlotta (Wiley, 2021)
In order to develop strategies for sustainable practices and to enhance the replacement of non-renewable materials with sustainable alternatives such as wood, it is essential to recognize the variables affecting consumers’ quality perceptions. Despite this, there is still limited knowledge about the perceived quality of wooden building materials. Wood industry studies have to date approached quality mainly by investigating quality indicators related to the product or supplier, while overlooking the effects of the consumer characteristics on the quality perception process. The purpose of this study is to fill this gap by implementing a systematic literature review of peer-reviewed articles published in international scientific journals during the 2000s using the “Scientific Procedures and Rationales for Systematic Literature Reviews” (SPAR-4-SLR) protocol. Literature searches are implemented in two scientific databases (ISI Web of Knowledge and Scopus) to gather the material to be analyzed according to two organizing frameworks (i.e., the TCCM framework and the Model of the Quality Perception Process). The results suggest that the perceived quality of wooden building materials is affected by different quality cues and attributes of wood (i.e., sensory, social, economic, technical, and sustainability properties). Furthermore, different personal variables (consumers’ socio-demographic and psychographic characteristics) and situational variables influence consumer behavior regarding wooden building materials. The study contributes to wood products literature by providing new theoretical insights about the perceived quality of wooden building materials and developing a future research agenda that brings forward a number of propositions for future studies based on identified research gaps.
Keywords: future research agenda; quality perception; systematic literature review; wood consumption; consumer behaviour; fi=Markkinointi|en=Marketing|